Implementation of Living Quran Culture in School - Kholis, Nur; Mufidah, Nuril; Indriharta, Lilik (Badan Litbang dan Diklat Kementerian Agama RI, 2019)
AbstractThis research has two aims, namely to describe the types of implementation of living Quran culture in schools, and to analyze the values that underlie the spirit of the development of a living Quran culture at school. The method of this research was qualitative using a case study approach, and conducted at SDI and SMPI Al Azhaar Tulungagung, East Java. The research subjects were the kiai of Islamic boarding schools, the chairman of the foundation, the principal, and the teachers. Data was collected through; in-depth interviews, documentation, and observation. The results of this study indicate that; First, the types of implementation of the Quran's living culture are a) Living Quran (tahfidz, iqra', tahsin, tarjim, Quran khotmil in student's house, Quran reciting competition, sticking verses Quran in each class, and praying using Quran verses); b). Birrul walidain (praying for parents, piety, politeness); and c) Islamic behavior at school and home. Secondly, the values of the underlying spirit of the living Quran include the Quran as a guide to life, reading Quran leads to reward, Quran as the source of information and knowledge in the world and the hereafter, and Quran as the holy book that carries the truth.Abstrak Penelitian ini memiliki dua tujuan. Pertama, untuk menggambarkan jenis-jenis implementasi budaya living Quran di sekolah. Kedua, menganalisis nilai-nilai yang mendasari semangat pengembangan budaya living Quran di sekolah. Metode penelitian ini adalah kualitatif dengan menggunakan pendekatan studi kasus. Penelitian ini dilakukan di SDI dan SMPI Al Azhaar Tulungagung, Jawa Timur, Indonesia. Subjek penelitian adalah kiai pesantren, ketua yayasan, kepala sekolah, dan guru. Artikel ini membahas jenis-jenis budaya dan nilai-nilai living Quran yang menjadi semangat implementasi. Data dikumpulkan melalui wawancara mendalam, dokumentasi, dan observasi. Validitas data diperiksa menggunakan teknik berikut; kredibilitas, transferabilitas, ketergantungan, dan konfirmabilitas. Analisis data dilakukan dalam siklus bertingkat mulai dari pengumpulan data, tampilan data, reduksi data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan; Pertama, jenis-jenis penerapan budaya living Quran adalah mendalami Quran (tahfidz, iqra', tahsin, tarjamah, khotmil Quran di rumah siswa, kompetisi membaca Quran, menempel ayat-ayat Quran di setiap kelas, dan salat menggunakan ayat-ayat Quran); Birrul walidain (berdoa untuk orang tua, kesalehan, kesopanan); dan Perilaku Islam di sekolah dan di rumah. Kedua, nilai-nilai semangat yang mendasari living Quran meliputi Quran sebagai pedoman hidup, membaca Quran mengarah pada pahala, Quran sebagai sumber informasi dan pengetahuan di dunia dan akhirat, dan Quran sebagai kitab suci yang membawa kebenaran.